Clinical application of Myxovirus resistance protein A as a diagnostic biomarker to differentiate viral and bacterial respiratory infections in pediatric patients - Zhu, Min; Chen, Lijin; Cao, Jiali; Cai, Jianguo; Huang, Shuying; Wang, Huibin; He, Huanjuan; Chen, Zimin; Huang, Rongfu; Ye, Huiming (Frontiers in Immunology, 2025)
BackgroundDifferentiating between viral and bacterial respiratory tract infections in pediatric patients remains a significant diagnostic challenge, often leading to the overuse of antibiotics. Myxovirus resistance protein A (MxA) has been identified as a promising biomarker for viral infections. This study aimed to assess the fluctuations in blood MxA levels among children with viral respiratory infections and to explore the differences in MxA levels between viral and bacterial infections, focusing on clinical implications for antibiotic use.MethodsWe conducted a retrospective study using enzyme-linked immunosorbent assay (ELISA) to measure MxA levels in a cohort of 314 children with respiratory tract infections and 89 healthy controls. The study compared MxA levels across children with viral, bacterial, and mixed infections. Diagnostic accuracy was evaluated using receiver operating characteristic (ROC) curve analysis to distinguish between viral and bacterial infections or between viral and co-infections, with additional comparisons to other established infection biomarkers.ResultsMxA levels were significantly elevated in children with viral infections (n=205) compared to bacterial infections (n=21) (p<0.0001). The ROC curve analysis demonstrated that MxA had an area under the curve (AUC) of 0.8019 (95% CI: 0.6989 to 0.9049) for distinguishing viral from bacterial infections. Combining MxA with C-reactive protein (CRP) further enhanced diagnostic performance, achieving an AUC of 0.8713 (95% CI: 0.7916 to 0.9510). However, the use of MxA or MxA/CRP alone is insufficient to differentiate viral and viral - bacterial coinfection. The AUC of MxA is 0.5161 (95% CI: 0.4392 to 0.5930), and the AUC of MxA/CRP is 0.5429 (95% CI: 0.4705 to 0.6153).ConclusionsThis study highlights the diagnostic potential of MxA as a biomarker for differentiating viral from bacterial respiratory infections in children. The combined use of MxA and CRP offers a novel approach to improve diagnostic accuracy. Still, a combination with other clinical and laboratory markers remains required to determine whether to administer antibiotics to children with respiratory tract infections.